Impact of mechanical deformation on guest diffusion in zeolitic imidazolate frameworks. Issue 10 (24th December 2015) - Zheng, Bin; Wang, Lian Li; Hui, Jia Chen; Du, Lifei; Du, Huiling; Zhu, Ming
Abstract : The effect of the elastic strain modes of MOFs on the guest diffusivity was presented and analysed. Abstract : The effect of the mechanical deformation of metal–organic frameworks on guest diffusion was investigated by employing molecular dynamics simulations. Two basic deformation modes, uniaxial tensile and shear deformation, were considered. The computed shear modulus of the zeolitic imidazolate framework-8 (ZIF-8) model system was much lower than the Young's modulus, which is in agreement with the experimental results. The diffusion rate in ZIF-8 was calculated for two types of guest molecules: the nonpolar H2 and the quadrupolar CO2 . Under tensile strain, the diffusion of both H2 and CO2 was found to be enhanced, whereas the diffusion rates did not change significantly under shear loading. The evolution of the internal structure of ZIF-8 was studied to determine its effect on guest diffusion. The organic–inorganic connection was identified as the source of the framework's flexibility, and therefore we focused on the N–Zn bond and the N–Zn–N angle. Under stretching deformation, the N–Zn bond is elongated and the N–Zn–N angle remains constant. Thus, the length of the C2–C2 long bond, determining the size of the 6-membered ring (6MR) gate, increases and the gate is opened, allowing for faster guest diffusion. Under shear deformation, the N–Zn bond length changes very little and the N–Zn–N angle is distorted. This results in the occurrence of three peaks in the C2–C2 bond length distribution. Although the 6MR gate is distorted, the variation of its average size is small, resulting in a very small effect on the guest diffusivity. In addition, we found that the fluctuation of the ZIF-8 cell can enhance the impact of the mechanical deformation of the host on guest diffusion.